The health system in Syria (2000–2024): assembling the pieces of a fragmented system—A scoping review - Orwa Al-Abdulla; Maher Alaref; Agneta Kallström; Jussi Kauhanen (Health Research Policy and Systems)
Abstract This study provides a detailed overview of Syria’s health system from 2000 to 2024 by synthesizing existing literature and data. Its goal is to inform the health sector recovery plan following recent political changes in Syria, detailing the health system’s characteristics and evolution on the basis of the WHO’s conceptual framework. A scoping review was conducted following Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines. Data sources included PubMed, MEDLINE, Scopus, Google Scholar, grey literature and government reports. The analysis identified service delivery, financing, and governance as the most frequently discussed aspects of the health system. It revealed a distorted health system that retained aspects of the Semashko model whilst also incorporating elements of liberalization from the 2003 modernization program. The study underscores major challenges, including the politicization of healthcare, workforce shortages, fragmented financing, and disparities in access to healthcare services. The findings indicate that the Syrian health system has been characterized by centralized governance, inconsistent financing strategies, a fragmented health information system, and a growing dependence on the private sector. The post-conflict recovery phase offers a chance to rebuild a more equitable and resilient health system. Policymakers are urged to consider necessary reforms to the health system recovery plan in Syria.